PENGARUH METODE MIMICRY MEMORIZATION TERHADAP HASIL BELAJAR MUFRODAT SISWA KELAS 2 MI THOLABUSSALAMAH - Laylatul Marfu’ah (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
This research presents "The Influence of the Mimicry-Memorization Method (Mim-Mem Method) on Mufrodat Mastery at Madrasah Aliyah Darul Lughah Wal Karomah". The purpose of using the Mimicry-Memorization Method (Mim-Mem Method) to master mufrodat at Madrasah Aliyah Darul Lughah Wal Karomah is to facilitate students' understanding and mastery of mufrodat on Arabic language learning material. The first step is for the teacher to pronounce the vocabulary followed by the students. This quantitative research method uses experimental research (trial) with ordinal data. Meanwhile, the data collection method uses an oral test method with comparative analysis techniques (non-parametric), namely the Mann-Whitney U-test (U Test). To prove whether this research is significant or not, researchers used SPSS (Statistical Package for the Social Sciences) data. The results of this data have proven that there is an influence of the Mimicry Memorization Method (Mim-Mem Method) on mastery of mufrodat at Madrasah Aliyah Darul Lughah Wal Karomah. By using this method, students are more active and more effective in studying Arabic subjects.